2023
DOI: 10.1001/jamanetworkopen.2022.52381
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Use and Quality of Opioid Use Disorder Treatment in the US During the COVID-19 Pandemic

Abstract: ImportanceLittle is known about the potential implications of the rapid transition to telehealth during the COVID-19 pandemic for treatment of opioid use disorder (OUD).ObjectiveTo examine the association between telemedicine adoption during the COVID-19 pandemic and indicators of OUD treatment quality.Design, Setting, and ParticipantsThis cohort study analyzed deidentified administrative claims data from OptumLabs Data Warehouse. Claims for telemedicine visits were included for both the prepandemic period (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…During the COVID-19 pandemic, temporary Drug Enforcement Administration (DEA) rules suspending in-person evaluation requirements for the initiation of controlled substance treatments, including both audio and audiovisual buprenorphine prescribing, allowed for expansion of bridge clinic services to a virtual environment ( Second Temporary Extension ). Buprenorphine therapy for OUD provided through a telemedicine platform can overcome some treatment obstacles, improve care engagement and retention, decrease overdose and mortality rates, and lower health care cost ( Hailu et al, 2023 , Guillen et al, 2021 , Jones et al, 2022 , Jones et al, 2023 ). Bridge clinics, especially those using telemedicine, can serve as a safety net to close gaps in the continuum of care which may arise for myriad reasons and cause diminished access to proven lifesaving care.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, temporary Drug Enforcement Administration (DEA) rules suspending in-person evaluation requirements for the initiation of controlled substance treatments, including both audio and audiovisual buprenorphine prescribing, allowed for expansion of bridge clinic services to a virtual environment ( Second Temporary Extension ). Buprenorphine therapy for OUD provided through a telemedicine platform can overcome some treatment obstacles, improve care engagement and retention, decrease overdose and mortality rates, and lower health care cost ( Hailu et al, 2023 , Guillen et al, 2021 , Jones et al, 2022 , Jones et al, 2023 ). Bridge clinics, especially those using telemedicine, can serve as a safety net to close gaps in the continuum of care which may arise for myriad reasons and cause diminished access to proven lifesaving care.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Studies comparing in-person and TM-based MOUD generally showed comparable effectiveness and even better retention outcomes in TM-based MOUD. [11][12][13] According to a recent study, the policy changes supportive of TM implemented during the COVID-19 pandemic had a positive effect on the access to health care and clinical outcomes of rural patients with OUD. 14 Thus, the provision of MOUD services via TM is a promising approach to quickly expand OUD treatment access in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Rural communities are of particular concern because they are disproportionately impacted by opioid use disorder (OUD) and encounter many challenges to accessing MOUD (eg, limited availability of MOUD services, economic distress, older populations, social isolation, and travel burden) 5–10 . Studies comparing in‐person and TM‐based MOUD generally showed comparable effectiveness and even better retention outcomes in TM‐based MOUD 11–13 . According to a recent study, the policy changes supportive of TM implemented during the COVID‐19 pandemic had a positive effect on the access to health care and clinical outcomes of rural patients with OUD 14 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The convenience of telehealth combined with the ability to obtain the prescription at a pharmacy is notable 3 and telehealth services have proliferated in response. 4,5 Prior studies evaluating the efficacy of teleMOUD are largely limited to descriptive articles and studies reporting rates of treatment retention. The results of these studies have so far been promising and suggest that teleMOUD is associated with significantly higher rates of retention.…”
Section: Introductionmentioning
confidence: 99%
“…2 The convenience of telehealth combined with the ability to obtain the prescription at a pharmacy is notable 3 and telehealth services have proliferated in response. 4,5…”
Section: Introductionmentioning
confidence: 99%